Increased Gonorrhea Screening and Case Finding After Implementation of Expanded Screening Criteria—Urban Indian Health Service Facility in Phoenix, Arizona, 2011–2013. Issue 6 (June 2016) - Patton, Monica E.; Kirkcaldy, Robert D.; Chang, Douglas C.; Markman, Stephanie; Yellowman, Marilyn; Petrosky, Emiko; Adams, Laura; Robinson, Candice; Gupta, Akash; Taylor, Melanie M.
Abstract : Background: Gonorrhea screening is recommended for women at risk and men who have sex with men; expanded screening is encouraged based on local epidemiology. In response to a substantial increase in gonorrhea cases at an urban medical center serving American Indians, gonorrhea screening of all sexually active patients aged 14 to 45 years was initiated in March 2013. We describe gonorrhea screening coverage and case finding before and after implementation of expanded screening. Methods: In March 2013, provider training, electronic health record prompts, and bundled laboratory orders were implemented to facilitate gonorrhea screening of all sexually active patients aged 14 to 45 years. We assessed the proportions of patients screened and testing positive for gonorrhea in the 2 years before (March 2011–February 2012 [indicated as 2011], March 2012–February 2013 [2012]) and 1 year after (March 2013–February 2014 [2013]) expanded screening measures. Results: Gonorrhea screening coverage increased from 22% (2012) to 38% (2013); coverage increased 50% among females and 202% among males. Screening coverage increased in nearly all clinics. Gonorrhea case finding increased 68% among females in 2013 (n = 104) compared with 2012 (n = 62), primarily among women aged 25 to 29 years. No corresponding increase in gonorrhea case finding occurred among males. Most increased case finding occurred in the emergency department. Conclusions: After introduction of expanded gonorrhea screening, there was a significant increase in gonorrhea screening coverage and a subsequent increase in gonorrhea case finding among females. Despite increased screening in all clinics, increased case finding only occurred in the emergency department. Abstract : Gonorrhea screening increased significantly after an urban medical center serving American Indians recommended screening all sexually active patients aged 14–45 years, but increased case finding only occurred among females.